CHANGES IN THE MORPHOLOGY AND POLYSACCHARIDE CONTENT OF MICROCYSTIS AERUGINOSA (CYANOBACTERIA) DURING FLAGELLATE GRAZING(1) - Yang, Zhou (Journal of phycology, 2008)
© 2008 Phycological Society of America.